The South African SHARE-TAVI registry: incidence and risk factors leading to conduction disturbances requiring permanent pacemaker implantation - Du Toit, Rudolf; Doubell, Anton; Abelson, Mark; Hellig, Farrel; Horak, Adie; Mabin, Thomas; Klug, Eric; Schaafsma, Elizabeth; Van Wyk, Jacques; Scherman, Jacques; et al. (SA Heart Journal, 2021)
Background: One of the most common complications post transcatheter aortic valve implantation (TAVI) is the development of heart block requiring permanent pacemaker implantation (PPM). The incidence of PPM in international registries ranges from 13% - 17.5%. Methods: The aim of this observational study was to report the PPM rate in the SHARE-TAVI registry and determine the clinical, electrocardiographic and procedural predictors of PPM as well as the effect of PPM on clinical outcomes. Results: Three hundred and fi ve subjects were analysed. The PPM rate was 9%. Third degree atrioventricular block at the time of implant was the most common indication for PPM. Self-expanding valves (PPM rate 14% vs. 6% for balloon-expandable valves, p=0.02) were correlated with the need for PPM. Baseline ECG predictors of PPM were axis deviation, QRS duration and conduction delay, most notably a pre-existing right bundle branch block (OR 15.88, p<0.01). PPM infl uenced functional class at 30 days, but not the need for repeat hospitalisation or mortality at 30-day and 1-year follow-up. Conclusions: A PPM rate lower than that reported in large international registries was found. Predictors of PPM and the infl uence of PPM on outcomes were similar to those reported in the international data.